2010
DOI: 10.1063/1.3290985
|View full text |Cite
|
Sign up to set email alerts
|

An NMR study of macromolecular aggregation in a model polymer-surfactant solution

Abstract: A model complex-forming nonionic polymer-anionic surfactant system in aqueous solution has been studied at different surfactant concentrations. Using pulsed-field-gradient diffusion NMR spectroscopy, we obtain the self-diffusion coefficients of poly͑ethylene glycol͒ ͑PEO͒ and sodium dodecyl sulfate ͑SDS͒ simultaneously and as a function of SDS concentration. In addition, we obtain NMR relaxation rates and chemical shifts as a function of SDS concentration. Within the context of a simple model, our experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 43 publications
4
45
0
Order By: Relevance
“…The a-CH 2 group is more susceptible to the extramicellar environment than CH 3 group, which resides in the core of SDS micelle. Hence, the chemical shift difference (Dd) between a-CH 2 and CH 3 is an indication of a change in the local environment of the SDS molecule [34]. The chemical shift difference between a-CH 2 and CH 3 of pure SDS is denoted by Dd 1 , whereas such difference in the presence of mixture-I and mixture-II are represented by Dd 2 and Dd 3 , respectively, and are plotted against SDS concentration depicted in Fig.…”
Section: Proton Chemical Shift Study Of Concentration Induced Micellimentioning
confidence: 99%
See 2 more Smart Citations
“…The a-CH 2 group is more susceptible to the extramicellar environment than CH 3 group, which resides in the core of SDS micelle. Hence, the chemical shift difference (Dd) between a-CH 2 and CH 3 is an indication of a change in the local environment of the SDS molecule [34]. The chemical shift difference between a-CH 2 and CH 3 of pure SDS is denoted by Dd 1 , whereas such difference in the presence of mixture-I and mixture-II are represented by Dd 2 and Dd 3 , respectively, and are plotted against SDS concentration depicted in Fig.…”
Section: Proton Chemical Shift Study Of Concentration Induced Micellimentioning
confidence: 99%
“…The diffusion coefficients thus obtained are translated into hydrodynamic radii and the corresponding R H 's for pure SDS are found to be 3.9 Å (unimers) and 44 Å (micelles). The former value (3.9 Å) corresponds to the hydrodynamic radius of all-trans N = 12 carbon chain of SDS molecule [34], whereas the latter (44 Å) represents the size of the SDS micelle. However, SDS exists in the form of unimers, mixed aggregates/micelles and free micelles in the presence of the polymer.…”
Section: Proton Self-diffusion Study Of Sds-p123 Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, 38 we have shown that mixed-species (polymer-surfactant) aggregates are easier to study than singlespecies (surfactant) aggregates because the dynamics of each species can be independently and simultaneously measured via complementary NMR experiments. This allows models of aggregate structure to be sufficiently constrained.…”
mentioning
confidence: 99%
“…It has been shown to be a reasonable approximation to assume that the surface-associated water is essentially stationary in comparison to the bulk water. 38,47 Thus, water diffusion coefficient obtained as a function of surfactant packing fraction report directly on the fraction of surface associated water. Fig.…”
mentioning
confidence: 99%